Brief Report: Smoking in Systemic Sclerosis: A Longitudinal European Scleroderma Trials and Research Group Study. Issue 11 (24th September 2018) - Jaeger, Veronika K.; Valentini, Gabriele; Hachulla, Eric; Cozzi, Franco; Distler, Oliver; Airó, Paolo; Czirják, Laszlo; Allanore, Yannick; Siegert, Elise; Rosato, Edoardo; Matucci‐Cerinic, Marco; Caimmi, Cristian; et al.
Abstract : Objective: Data on the role of tobacco exposure in systemic sclerosis (SSc; scleroderma) severity and progression are scarce. We aimed to assess the effects of smoking on the evolution of pulmonary and skin manifestations, based on the European Scleroderma Trials and Research group database. Methods: Adult SSc patients with data on smoking history and a 12–24‐month follow‐up visit were included. Associations of severity and progression of organ involvement with smoking history and the Comprehensive Smoking Index were assessed using multivariable regression analyses. Results: A total of 3, 319 patients were included (mean age 57 years, 85% female); 66% were never smokers, 23% were ex‐smokers, and 11% were current smokers. Current smokers had a lower percentage of antitopoisomerase autoantibodies than previous or never smokers (31% versus 40% and 45%, respectively). Never smokers had a higher baseline forced expiratory volume in 1 second/forced vital capacity (FEV1 /FVC) ratio than previous and current smokers ( P < 0.001). The FEV1 /FVC ratio declined faster in current smokers than in never smokers ( P = 0.05) or ex‐smokers ( P = 0.01). The baseline modified Rodnan skin thickness score (MRSS) and the MRSS decline were comparable across smoking groups. Although heavy smoking (>25 pack‐years) increased the odds of digital ulcers by almost 50%, there was no robust adverse association of smoking with digital ulcer development. Conclusion: The known adverse effect of smoking on bronchial airways and alveoli is also observed in SSc patients; however, robust adverse effects of smoking on the progression of SSc‐specific pulmonary or cutaneous manifestations were not observed.